A review of rutting in asphalt concrete pavement - Albayati, Amjad H. (Open Engineering (Warsaw), 2023)
Undoubtedly, rutting in asphalt concrete pavement is considered a major dilemma in terms of pavement performance and safety faced by road users as well as the road authorities. Rutting is a bowl-shaped depression in the wheel paths that develop gradually with the increasing number of load applications. Heavy axle loadings besides the high pavement summer temperature enhance the problem of rutting. According to the AASHTO design equation for flexible pavements, a 1.1 in rut depth will reduce the present serviceability index of relatively new pavement, having no other distress, from 4.2 to 2.5. With this amount of drop in serviceability, the entire life of the pavement in effect has been lost. Therefore, it is crucial to look at the mechanism, possible reasons, as well as techniques, to reduce the rutting in order to offer long service life and safe roadways. To this end, the need has been arising for this research which deals mainly with a thorough review of the existing literature to highlight some key points for the researchers and pavement engineers related to rutting mechanism, measurement, and criteria, both intrinsic (mixture variables) and extrinsic (traffic and temperature) contributory factors to rutting, material characterization, test methods, and prediction methodologies, as well as possible ways to minimize the rutting distress in asphalt concrete pavement. So far, this research attempts to bridge the gap in the literature that frequently only addresses a single aspect of rutting by providing an in-depth review of rutting in asphalt concrete and thereby offers a complete comprehensive understanding of this major distress type.